Exploring information needs among family caregivers of children with intellectual disability in a rural area of South Africa: a qualitative study - Mantji Juliah Modula; Mpho Grace Chipu (BMC Public Health, 2024)
Abstract Background Globally, families experience challenges caring for and raising children with intellectual disability (ID). Family caregivers in rural states are mostly known for lacking support resources, including information on understanding the care of ID. Lack of adequate information on understanding of ID compromises the provision of life-long care and support of the children with ID’s physical, emotional, psychological and social developmental well-being. The study aimed to explore the information needs of family caregivers regarding the care of children with ID in rural areas of Limpopo Province, South Africa. Methods This qualitative explorative research conducted 16 in-depth individual interviews and one focus group discussion with ten family members. The participants shared their experiences of raising children with ID in rural communities. Inductive thematic analysis using Atlas Ti software categorised emerging themes and subthemes of this study from merged data sets on information needs regarding the care of children with ID among family caregivers. Results The findings highlighted the need for information regarding ID care among family caregivers raising children with ID in the home environment. The information challenges experienced by family caregivers include caring for the challenging behaviour of children with ID and available support resources and services for the children and their families. These challenges impact the care and support required to meet the developmental needs of children with ID. Furthermore, inadequate information on ID among family caregivers in rural communities with a lack of resources restricts the children from accessing required support services. Conclusions Given the information challenges these families face on ID, the stakeholders must develop continuous training programmes that will equip, empower, and further monitor ID care and management among family caregivers to enhance care and the raising of children with dignity.